An enhanced control strategy based imaginary swapping instant for induction motor drives - Iliass Rkik; Mohamed El Khayat; Abdelali Ed-Dahhak; Mohammed Guerbaoui; Abdeslam Lachhab (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The main aim of this paper is to present a novel control approach of an induction machine (IM) using an improved space vector modulation based direct torque control (SVM-DTC) on the basis of imaginary swapping instant technique. The improved control strategy is presented to surmount the drawbacks of the classical direct torque control (DTC) and to enhance the dynamic performance of the induction motor. This method requires neither angle identification nor sector determination; the imaginary swapping instant vector is used to fix the effective period in which the power is transferred to the IM. Both the classical DTC method and the suggested adaptive DTC techniques have been carried out in MATLAB/SimulinkTM. Simulation results shows the effectiveness of the enhanced control strategy and demonstrate that torque and flux ripples are massively diminished compared to the conventional DTC (CDTC) which gives a better performance. Finally, the system will also be tested for its robustness against variations in the IM parameters.